(17/20+2 13/20) + (6 7/25-2 10/25)= 3 + 3 22/25= 6 22/25
7 22/25
Пошаговое объяснение:
(1 7/20+2 13/20)+(6 7/25-2 10/25) переводим в неправильную дробь и получаем: (27/20+53/20)+(157/25-60/25)ну после решаем это выражение и получаем 4+3 22/25=7 22/25 или =7,88
(17/20+2 13/20) + (6 7/25-2 10/25)= 3 + 3 22/25= 6 22/25
7 22/25
Пошаговое объяснение:
(1 7/20+2 13/20)+(6 7/25-2 10/25) переводим в неправильную дробь и получаем: (27/20+53/20)+(157/25-60/25)ну после решаем это выражение и получаем 4+3 22/25=7 22/25 или =7,88